2018
DOI: 10.1136/archdischild-2018-315125
|View full text |Cite
|
Sign up to set email alerts
|

Big data and stratified medicine: what does it mean for children?

Abstract: Stratified medicine in paediatrics is increasingly becoming a reality, as our understanding of disease pathogenesis improves and novel treatment targets emerge. We have already seen some success in paediatrics in targeted therapies such as cystic fibrosis for specific cystic fibrosis transmembrane conductance regulator variants. With the increased speed and decreased cost of processing and analysing data from rare disease registries, we are increasingly able to use a systems biology approach (including ‘-omics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Extant empirical studies often assumed that MCNs are exogenous and found that medical collaborative practices may be affected by factors at individual, organizational, and system levels, such as mutual trust [20,21], IT infrastructure [22][23][24], medical policies, investment of public funds [9], and remuneration methods [4]. However, the conclusions drawn regarding the influence of these factors are inconsistent and contradictory [5].…”
Section: Transaction Efficiency Of Medical Servicesmentioning
confidence: 99%
“…Extant empirical studies often assumed that MCNs are exogenous and found that medical collaborative practices may be affected by factors at individual, organizational, and system levels, such as mutual trust [20,21], IT infrastructure [22][23][24], medical policies, investment of public funds [9], and remuneration methods [4]. However, the conclusions drawn regarding the influence of these factors are inconsistent and contradictory [5].…”
Section: Transaction Efficiency Of Medical Servicesmentioning
confidence: 99%
“…Children's rights and interests may be furthered through sophisticated analyses of data across domains -from clinical to environmental to educational. In the health context, big data in the form of -omics data has begun to show success in the stratification of sick children (Ding et al, 2019). The Committee on the Rights of the Child has encouraged States to conduct research with children "to learn about their health challenges, developmental needs, and expectations as a contribution to the design of effective interventions and health programs" (United Nations Committee on the Rights of the Child, 2013a).…”
Section: Children's Data: Opportunities and Challengesmentioning
confidence: 99%
“…They provide information query and connects medical services through Internet and big data technology, such as Baiyulan remote consultation platform, district-level imaging and inspection center, and various Internet hospitals, such as Chunyu Doctor, Hao Doctor, Pingan good Doctor, Dingxiang and Weiyi etc. This kind of medical transaction service platform can more easily obtain or even integrate all kinds of medical resources, and facilitate patients' medical opportunities [13,26]. There is another kind of platform, such as Changankang wechat platform for rectal cancer patients, which helps patients integrate all kinds of medical resources and design personalized treatment according to different course of disease.…”
Section: Scope Of Division Of Labormentioning
confidence: 99%
“…The establishment and operation of medical transaction service platform needs the investment of technology, labor and capital. These investments constitute a fixed learning cost for medical transaction services, which has been changed dramatically with the development of the Internet and big data technologies [13]. The fixed learning cost of medical transaction services will affect decision-maker division of labor and the level of specialization within medical transaction service.…”
Section: Role Generation Model: Specification Of the Unified Decision Modelmentioning
confidence: 99%
See 1 more Smart Citation